PEMANFAATAN HASIL HUTAN BUKAN KAYU SEBAGAI KERAJINAN ANYAMAN OLEH MASYARAKAT DI DESA KUALA DUA KECAMATAN KEMBAYAN KABUPATEN SANGGAU - Sasmita, Dayang Fatimah; Diba, Farah; Setyawati, Dina (Universitas Tanjungpura, 2021)
The community at Kuala Dua village, Kembayan sub district, Sanggau Regency has used non timber forest product for handicraft. The research purposes were to identified the raw material of non-timber forest product which used by the community to produce handicraft. The methods used in depth interview with the community. The respondent was chosen by snowball sampling. Total number of respondents was 14 persons. Â Result of the research showed that 4 non timber forest product used for handicraft. Â The plant used were bambu tali (Gigantochloa apus), nipah (Nypa fruticans), resam (Distranopteris linearis), and rotan lilin (Calamus javensis). The product was used for daily live and also sell to the market. Bambu tali was made into bakul and ketoro, nipah leaf was made into roof material, resam was made into ring and rotan lilin was made into basket, dish and Â cupboard.Keywords: Calamus javensis, Distranopteris linearis, Gigantochloa apus, handicraft, Nypa fruticans